2005
DOI: 10.1063/1.2009648
|View full text |Cite
|
Sign up to set email alerts
|

The recollapse problem of closed Friedmann–Robertson–Walker models in higher-order gravity theories

Abstract: We study the closed universe recollapse conjecture for positively curved FRW models with a perfect fluid matter source and a scalar field which arises in the conformal frame of the R + αR 2 theory. By including ordinary matter, we extend the analysis of a previous work. We analyze the structure of the resulted fourdimensional dynamical system with the methods of the center manifold theory and the normal form theory. It is shown that an initially expanding closed FRW universe, starting close to the Minkowski sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…System (21) is invariant under the transformation t → −t, y → −y (which implies that all trajectories are symmetric with respect to the r axis) and the line r = 0 is invariant. Note also that the system (21) has invariant lines y = ±2r (compare with the similar system in [41]). The behaviour of the solutions depends on the parameter γ and as we shall see, γ = 1 is a bifurcation value.…”
Section: Flat Modelsmentioning
confidence: 93%
“…System (21) is invariant under the transformation t → −t, y → −y (which implies that all trajectories are symmetric with respect to the r axis) and the line r = 0 is invariant. Note also that the system (21) has invariant lines y = ±2r (compare with the similar system in [41]). The behaviour of the solutions depends on the parameter γ and as we shall see, γ = 1 is a bifurcation value.…”
Section: Flat Modelsmentioning
confidence: 93%
“…For homogeneous and isotropic spacetimes in the Einstein frame this conjecture was found to be true for vacuum models [8] and for models with a perfect fluid with equation of state p = (γ − 1)ρ, 2/3 < γ < 2 [9]. More precisely it was shown that, an initially expanding closed FRW universe, starting close to the Minkowski spacetime cannot avoid recollapse.…”
Section: Cosmological Considerationsmentioning
confidence: 97%
“…Furthermore, the system (8) is not an arbitrary "free" four-dimensional system. In view of the 0 − 0 equation, the variables have to satisfy the constraint (9). The nonlinear coordinate transformation (14) is valid in a neighbourhood of the origin, small enough to ensure that the new variables still respect the constraint (9).…”
Section: Cosmological Considerationsmentioning
confidence: 99%
“…The zero minimum at φ = 0 of this potential is stable, but it cannot provide the mechanism for the late-time acceleration since V and H asymptotically approach to zero [156,157,192]. On the other hand, concerning the upper asymptote of V as φ → +∞, it follows that the potential has exponential order zero (see definition 2) as φ → +∞.…”
Section: Basic Frameworkmentioning
confidence: 99%
“…Preceding works for a large variety of non-negative potentials are [151,152,153,154,155,156,157,158]. In the reference [158], it have been extended many of the results obtained in [156] by considering arbitrary potentials.…”
Section: Introductionmentioning
confidence: 99%